The impact of intermittent normobaric hypoxia-hypoxic training on the blood and biochemical parameters of an athlete - Sheshurina T.A.; Slepova D.A.; Kalinin A.V.; Dorofeykov V.V.; Lomazova E.V. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to assess the impact of intermittent hypoxia-hypoxic training on the biochemical and hematological characteristics of an athlete. Methods and structure of the study. The research involved a group of ten male athletes aged 16 to 17, who were swimmers and had achieved the level of first-category sports and were candidates for master of sports. The athletes were in the preparatory phase of their training. All participants underwent a series of interval normobaric hypoxia-hypoxic training sessions using the OXYTERRA device, a Russian-made device. The training protocol consisted of five cycles, each cycle consisting of five minutes of hypoxia (oxygen concentration of 13%) followed by three minutes of hyperoxia (oxygen concentration of 32%). Results and conclusions. It has been confirmed that of interval normobaric hypoxia-hypoxic training results in a rise in hemoglobin levels following a series of treatments for athletes who engage in swimming. The analysis revealed statistically significant variations in lactate dehydrogenase activity before and after the treatment cycle, indicating an enhancement in the delivery of oxygen to tissues and an activation of recovery processes in athletes.